Studi Meta-Analisis Pengaruh Pendekatan STEM (Science, Technology, Engineering, Mathematics) Terhadap Kemampuan Literasi Sains Siswa - Irpan Irpan; Yoga Budi Bhakti; Asep Setiadi (UNIVERSITAS INDRAPRASTA PGRI, 2022)
This study aims to determine the effect size of the STEM approach on students scientific literacy skills in science and physics learning. The research method used is descriptive analysis of the results of scientific publications in national e-journals. The effect of studies that apply the STEM approach to scientific literacy skills and are analyzed using meta-analysis techniques. The findings based on the effect size study on the literacy ability of sians based on science and physics learning revealed that the overall results of the study showed an Effect Size of 0,364 in the large effect category. The STEM approach also has an influence on education levels, areas and research-related variables such as scientific literacy skills, science competencies, problem-solving abilities and students' conceptual understanding. The conclusions of this study indicate that the learning approach with the STEM approach in science and physics learning is able to provide a positive result distribution on students' scientific literacy skills in learning.